Beyond Microcephaly: Semilobar Holoprosencephaly with Marked Macrocephaly due to Severe Congenital Hydrocephalus, Brachycephaly, and Hyponatremia – A Case Report - Cynthia Cynthia; Edbert Wielim; Regina Suriadi; Putu Siska Suryaningsih (HM Publisher, 2025)
Holoprosencephaly (HPE) is a rare, complex brain malformation arising from incomplete prosencephalon cleavage, typically associated with microcephaly and facial dysmorphism. Coexisting severe hydrocephalus leading to macrocephaly in HPE, particularly the semilobar type, presents a distinct clinical picture. Hyponatremia often complicates neurological conditions involving increased intracranial pressure, potentially worsening prognosis. The aim of this case report is to meticulously describe the clinical presentation, diagnostic evaluation, management approach, and early outcomes of this rare and complex neonatal neurological disorder. A male neonate, born at 35+3 weeks gestation to a mother with severe preeclampsia, presented with marked macrocephaly (head circumference 50 cm), a prominent fontanel, and bilateral sunset eyes. Initial CT scan confirmed hydrocephalus. Subsequent evaluation and a repeat CT scan at one month revealed brachycephaly (cephalic index 98) and semilobar holoprosencephaly. Head circumference progressed to 64 cm by the time of ventriculoperitoneal (VP) shunt surgery at approximately 5 weeks of age. Laboratory investigations showed hyponatremia (120 mEq/L), hyperkalemia, and hypochloremia. At three months, the patient exhibited significant growth and developmental delays and malnutrition. In conclusion, this case highlights an unusual presentation of semilobar HPE characterized by severe congenital hydrocephalus causing marked macrocephaly, rather than microcephaly, complicated by brachycephaly and significant hyponatremia. Early, comprehensive diagnostic evaluation and multidisciplinary management are crucial in such complex neurodevelopmental disorders to address multifaceted challenges and attempt to optimize outcomes.